Influence of Teacher Perceptions and Self-Efficacy in Teaching Science in Kindergarten - Syamsuyurnita, Syamsuyurnita; Vickery, Tina; Pardilla, Herli; Frazer, Mellissa (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: Early childhood science education forms the foundation for students' scientific literacy and inquiry skills. Teacher perceptions and self-efficacy beliefs significantly influence the quality and frequency of science instruction in kindergarten settings. Understanding these factors is crucial for improving early science education outcomes. This study aimed to examine the relationship between kindergarten teachers' perceptions of science teaching and their self-efficacy beliefs, and to determine how these factors influence science instruction practices in Indonesian kindergarten settings. Materials and methods: A quantitative cross-sectional study was conducted with 135 kindergarten teachers from 27 kindergarten institutions in Pekanbaru City, Indonesia. Data were collected using validated questionnaires measuring teacher perceptions of science teaching importance, self-efficacy beliefs, and science teaching practices. Statistical analyses were performed using SPSS version 29.0. Results: Results revealed a significant positive correlation (r = 0.742, p < 0.001) between teacher self-efficacy and frequency of science instruction. Teachers with higher self-efficacy scores (M = 4.23, SD = 0.58) demonstrated more positive perceptions toward science teaching compared to those with lower self-efficacy (M = 3.45, SD = 0.72). Multiple regression analysis indicated that self-efficacy beliefs explained 55.1% of the variance in science teaching practices. Conclusions: Teacher self-efficacy emerged as the strongest predictor of effective science instruction in kindergarten settings. Professional development programs focusing on enhancing teacher confidence and competence in science education are essential for improving early childhood science learning outcomes.